Optimization of Village Fund Management in Pasar V Village, Indonesia - Nori Susanda; Ipah Ema Juniati; Fatia Fatimah (Golden Ratio of Auditing Research, 2026)
This study aims to evaluate the management of Village Funds in Pasar V Natal Village in accordance with the Indonesian Minister of Home Affairs Regulations Number 20 of 2018 and 2020. The evaluation focuses on the stages of planning, implementation, administration, reporting, and accountability, and analyzes how they can be optimized to achieve outputs, outcomes, and impacts. The research employs a descriptive qualitative method with a case study approach. Primary data was collected through in-depth interviews with key informants (Village Head, Head of the Village Consultative Body (BPD), Financial Officer, Community Section Head, Community Leader, and a representative from the Community Empowerment Agency) and direct observation. Secondary data was obtained from document studies of the Village Budget (APBDes), financial reports, and relevant regulations. Data analysis was conducted interactively (data reduction, data display, and conclusion drawing) and validated through triangulation of sources and methods. The results indicate that the management of Village Funds in Pasar V Natal Village has been carried out in accordance with regulations in an administrative sense. All stages were executed in accordance with the principles of transparency and accountability, as evidenced by Village Deliberations (Musdes), public information boards, and tiered reporting. The outputs generated include infrastructure development (farm access roads and clean water facilities) and empowerment programs (MSME training and cash-for-work). The outcomes include improved quality of life, reduced unemployment rates, and increased Village Development Index (IDM) status. The long-term impact, beginning to emerge, is the strengthening of the local economy and of village self-reliance.